Pengembangan pangan fungsional berbasis tepung okara dan tepung beras hitam (Oryza sativa L. indica) sebagai makanan selingan bagi remaja obesitas - Adiari, Ni Wayan Lisa; Yogeswara, Ida Bagus Agung; Putra, I Made Wisnu Adhi (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2017)
Background : Obesity is an excessive build up of fat in the body thus causing weight far above normal and it can improve the risk of degenerative dissease. Increasing food consumption of high protein, fiber and antioxidants could  solve obesity problem. Soyabean milk waste product (okara) has high protein content but low economic value. Black rice flour has high antosianin, antioxidan and fiber. Functional food with main composition okara and black rice flour could  be an alternative as a  functional food for this matter.Objective : To investigate right formulation of snack bar based on nutritional content and  sensory caracteristic for obese adolescent.Methods : This type of research is an experimental study using Complete Randomized Design with three treatments (Formula I, II, and III) and performed two replications (duplo). Nutritional value data between group  was analyzed using Analysis of Variance (ANOVA) while sensory characteristic were tested by calculating hedonic quality test score.Result : Statistical analysis of nutritional content showed there were significantly different between group (p<0.05), but for antioxidants and phenolics levels and analysis of the sensory quality test were not significantly different (p>0.05). Formula I was most preferred and favored by the panelists with energy content 125.64 g, 9.89% water, 3.13% ash, 19.6% protein, 12.41% fat, 45.07% Carbohydrate, 16.44% total sugar, 15.58 % crude fiber, 208.35 mg/L GAEAC antioxidant, 1.01 mg/100 g anthocyanin and 61.05 mg/100 GAE phenolic.Conclusion : Formula I was the most preferred snack bar by panelist. This formula recommended for obese adolescent.